EFFICACY OF AN EXPERIMENTAL MODEL OF NON-ALCOHOLIC FATTY LIVER DISEASE BASED ON A HIGH-FAT DIET WITH CHOLESTEROL - Pivtorak, V.I.; Sydorenko, B.V.; Monastyrskyi, V.M.; Pivtorak, K.V.; Bulko, M.P. (World of Medicine and Biology, 2022)
The purpose of the study was to establish the effectiveness and informativeness of the experimental model of non-alcoholic fatty liver disease based on high-fat diet and cholesterol in the experiment. The studies were performed on 60 white nonlinear adult male rats, weighing 180–200 g at the beginning of the experiment. During the experiment, the use of high-fat diet and cholesterol for 60 days resulted in an increase in body weight, rat body mass index, liver mass and liver mass index, increase in activity of alanine aminotransferase and aspartate aminotransferase, hyperglycemia. Morphological changes of liver tissues were characterized by fatty degeneration of hepatocytes, which had the form of microvesicular and macrovesicular vacuolation with deformation of the nuclei and their displacement to the periphery of the cell, a change in the size of the sinusoids. It is important to bring the experimental model as close as possible to the mechanisms of non-alcoholic fatty liver disease in humans.